Translation and validation of the Brazilian version of the Physical Appearance Comparison Scale-Revised in college women - Claumann G.S.* (2021)
© 2021 Elsevier LtdBrazilian women are known to present high levels of physical appearance concerns, and data suggest they often compare themselves with others. Nevertheless, there is no validated instrument to systematically assess appearance comparisons in the Brazilian population. Thus, this study aimed to translate the Physical Appearance Comparison Scale-Revised (PACS-R) into Brazilian Portuguese and evaluate its factor structure, internal consistency, and convergent validity in Brazilian college women. The translated version into Brazilian Portuguese of the PACS-R was completed by 832 Brazilian college women and its factor structure was examined through exploratory and confirmatory factor analyses, internal consistency through McDonald's omega, and convergent validity through its associations with measures of eating disorder symptoms, internalization of appearance ideals, appearance-related sociocultural pressures, body satisfaction, and self-esteem. The results suggested an 11-item single-factor scale. The Brazilian Portuguese PACS-R showed adequate internal consistency and was significantly associated with all measures of convergent validity in the expected direction, indicating its adequate convergent validity. The Brazilian Portuguese PACS-R might be useful in the investigation of the appearance comparison among women in Brazil, as also in the study of body image and eating disorders.